2019
DOI: 10.1002/jlb.mr0618-241rr
|View full text |Cite
|
Sign up to set email alerts
|

OMIC signatures to understand cancer immunosurveillance and immunoediting: Melanoma and immune cells interplay in immunotherapy

Abstract: Melanoma is the deadliest form of skin cancer. Cutaneous melanomas usually originate from exposure to the mutagenic effects of ultraviolet radiation, and as such they exhibit the highest rate of somatic mutations than any other human cancer, and an extensive expression of neoantigens concurrently with a dense infiltrate of immune cells. The coexistence of high immunogenicity and high immune cell infiltration may sound contradictory for cancers carrying a gloomy outcome. However, recent studies have unveiled a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 152 publications
(280 reference statements)
0
16
0
Order By: Relevance
“…Melanoma is one of the most aggressive forms of skin cancer, it accounts for only 5% of all skin cancer cases, but 80% of all skin cancer deaths (44). The occurrence, development, and evolution of melanoma are based on the accumulation of genomic changes, including high ultraviolet-driven mutation burdens, which makes melanoma the most immunogenic tumor (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is one of the most aggressive forms of skin cancer, it accounts for only 5% of all skin cancer cases, but 80% of all skin cancer deaths (44). The occurrence, development, and evolution of melanoma are based on the accumulation of genomic changes, including high ultraviolet-driven mutation burdens, which makes melanoma the most immunogenic tumor (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…As many other cancer types, melanoma can provoke an intricate and multifaceted immune response which can be more or less deleterious for the tumor, depending on several factors (86,87). The involvement of autophagy in this context can very much depend on where it is exerting a major function in regulating the immune response and which immune cells are sensing and then responding to the different levels of autophagy (88)(89)(90)(91). For instance, the group of Verginis demonstrated that autophagy inhibition in myeloid-derived suppressor cells (MDSCs), a population of immune cells accumulating within the tumors with the function of suppressing the immune response (92), can redirect these cells toward an antitumor immune reaction (93).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting how these progenitor exhausted T cells converge as an important population for cancer control in both immunization and immunotherapy strategies. Understanding how these T cell populations are formed and modulated will be decisive for strategies of cooperative therapies, particularly because of the high number of patients with tumors refractory to immunotherapy or that relapse after an initial positive response (3,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…The tumors width and length were measured using a caliper every 2 days starting at day 7. The tumor volume was calculated as 4/3p (1/2 width) 2 (1/2 length), in mm 3 . Tumor appearance was scored daily through manual palpation, and mice with no evidence of tumor by the end of the following period were scored as tumor-free.…”
Section: Melanoma Culture and Tumor Challengementioning
confidence: 99%